Nonlinear Performance of Composite Cold-formed Steel Joints with Lightweight Concrete: An Experimental and Computational Study - Faisal, Amsyar; Tan, Cher Siang; Arizu, Sulaiman (Academy of Sciences Malaysia, 2025)
Semi-rigid composite cold-formed steel joints are widely used in contemporary buildings and constructions because of their well-known structural advantages and cost-effectiveness. Cold-formed steel enhances structural performance through its favourable strength-to-weight ratio, corrosion resistance and ease of fabrication. This study examines the mechanical behaviour of a composite connection between cold-formed steel and lightweight concrete, aiming to analyze the factors influencing its ultimate moment resistance, initial stiffness, and failure modes. A total of 14 composite cold-formed steel joint specimens are tested in a full-scale isolated joint experiment. Various factors were imposed on these samples, such as different sizes of tension bolts, varying thicknesses of gusset plate connectors, densities of lightweight aggregate concrete, slab thicknesses, and diameters of reinforcing bars. Computational ABAQUS tool is used for numerical modelling to verify and analyze how varying geometrical factors impact the mechanical characteristics of composite cold-formed steel joint structures. Strength ratios between 0.90 and 1.17 demonstrate strong correspondence between experimental and numerical results in the moment-rotation analysis. This study was able to provide valuable insights and a framework for an in-depth examination of the capabilities and durability of semi-rigid or partially rigid composite steel constructions.